Susceptibility to e-cigarette use and associated factors in high school youth, Oklahoma Youth Tobacco Survey, 2021-2022 - Shirley A. James; Ashley H. White; Fahad F. Kahn; Nasir Mushtaq; Sixia Chen; Laura A. Beebe (Frontiers Media S.A., 2024)
IntroductionSusceptibility predicts subsequent uptake of e-cigarettes (EC) by youth. This study identified factors associated with EC susceptibility among high school students who have never used a tobacco/nicotine product.MethodsThe Oklahoma Youth Tobacco Survey was administered to a random sample of 36 Oklahoma High Schools during the 2021-2022 school year (n = 1,220 participating students). Associations between EC susceptibility and covariates were identified using stepwise logistic regression for weighted survey data.ResultsMore than one third of Oklahoma high school students who had never used tobacco or nicotine products (36.4%) were susceptible, and males had higher susceptibility than females (38.8 and 33.9%, respectively). In males, EC susceptibility was associated with race (Black, American Indian, and other were less susceptible), psychological distress (aOR = 2.4, 95% CI = 1.1, 4.8), disagreement that all tobacco products are dangerous (aOR = 3.1, 95% CI = 1.2, 7.9), and perception of little/no harm from secondhand vapor (aOR = 3.4, 95% CI = 2.1, 5.3). In females, identifying as gay, lesbian, or bisexual (aOR = 2.1, 95% CI = 1.1, 3.9), poor academic performance (aOR = 4.5, 95% CI = 1.6, 12.6), psychological distress (aOR = 2.6, 95% CI = 1.2, 5.5) and interacting with EC content on social media (aOR = 5.9, 95% CI = 1.9, 18.1) were associated with EC susceptibility.ConclusionMales and females had different patterns of susceptibility to EC use. Understanding groups of adolescents most susceptible to using nicotine products can help target prevention efforts at home, in schools, and within communities.